(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The article presents experimental studies of the roughness by surface plastic deformation (SPD) on flat surfaces of steel 45. A dispersion analysis was used to study the influence of various factors on the surface quality. From the experimental studies and the dispersion analysis made, a graphical interpretation of the main effects was obtained. Graphical visualizations of the roughness pattern after SPD on the processed surfaces were obtained. Overlapping sinusoidal movements of the deforming spherical element were realized.